Hormonal control of flight metabolism in Odonata? - Janssens, Markus Peter-Erik (Department of Biological Sciences, 2016)
Members of the AKHIRPCH family of peptides were identified in corpora cardiaca of the dragonfly Anax imperator (Anisoptera: Aeshnidae), Orthetrumjuliajalsum (Anisoptera: Libellulidae) and the damselflies Pseudagrion inconspicuum and Ischnura senegalensis (Zygoptera: Coenagrionidae). After isolation ofthe peptides by reversed phase high performance liquid chromatography, the primary structures were established by Edman sequencing and mass spectrometry (Ani-AKH: pGlu-Val-Asn-Phe-Ser-Pro-Ser-TrpNH 2 ), (Lia-AKH: pGlu-Val-Asn-Phe¬ Thr-Pro-Ser- TrpNH 2 ) and (Psi-AKH: pGlu- Val-Asn-Phe- Thr-Pro-Gly- TrpNH 2 ). One corpus cardiac of A. imperator contains about 40 pmol Ani-AKH, O. julia 19-24 pmol Lia¬ AKH and P. inconspicuum about 2.4 pmol Psi-AKH. Injection of Ani-AKH (3.4 pmol) increased the concentration of haemolymph lipids in A. imperator. Lia-AKH (l pmol) similarly had an adipokinetic effect in 0. julia. Psi-AKH (I pmol) had an adipokinetic effect, as well as a small hyperglycaemic effect in P. inconspicuum. The AKH peptides of other Odonata were investigated. In the suborder Anisoptera, Ani-AKH was identified in representatives of the Aeshnidae, Cordulegasteridae, and possibly the Corduliidae. Lia¬ AKH was identified in representatives of the Libellulidae and Gomphidae. In the suborder Zygoptera, Psi-AKH was identified in representatives of the families Chlorolestidae, Lestidae and Chlorocyphidae, and possibly the Calopterygidae and Protoneuridae. Classification of Odonata according to their flight behaviour as "perchers" or "fliers" is supported by parameters of energy metabolism. Lipid metabolism seems to have a greater importance in fliers than perchers. The lipid concentration in the haemolymph is highest in the flier A. imperator, intermediate in the percher 0. julia and lowest in the percher P. inconspicuum. There are indications that mitochondria isolated from flight muscles of A. imperator may have a higher capacity for lipid oxidation than 0. julia. The contribution of carbohydrates to flight metabolism seems to be more important in perchers than in fliers. The concentration of carbohydrates in the haemolymph is highest in P. inconspicuum, intermediate in O. julia and lowest inA. imperator. The maximal activity of phosphofructokinase (a rate-limiting enzyme of glycolysis) is higher in the percher, O. julia, than in the flier, A. imperator. The lipid concentration in the haemolymph is higher than that of the carbohydrates in O. julia, A. imperator and P. inconspicuum. Palmitoyl-carnitine is oxidised at high rates by isolated mitochondria from flight muscles of O. julia andA. imperator, similar to Locusta migratoria. Lipid is the major fuel utilised during flight in O. julia. Carbohydrates (in the haemolymph) and proline (in the haemolymph and flight muscles) are utilised as minor fuels. It is concluded that the processes of lipid metabolism provide the major source of energy during flight in Odonata. The AKH peptides seem to play a role in regulating lipid mobilisation during flight in Odonata.